2022
DOI: 10.1002/mame.202200256
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Electrospun Aligned Poly(lactic acid)/Collagen Fibers with Nanoporous Surface for Peripheral Nerve Tissue Engineering

Abstract: It is important for the functional recovery of defective nerves to construct a suitable microenvironment for nerve regeneration by optimizing the topological structure and biological functions of nerve grafts. Electrospun fibers are employed to mimic the extracellular matrix (ECM) and the effect of the porous features on fiber surface draws much attention. Yet, little is known about the effect of the nanotopology of the fiber surface in conjunction with collagen I (COL) on neural cells. Herein, poly(lactic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…This study reveals that the sensitivity of aerogel exceeds that of nanofibers. This difference may be attributed to the higher porosity of silica aerogel, which can range from 80% to 99.8% [ 4 , 5 , 6 , 7 , 8 ], compared to that of silica nanofibers, which typically exceed 80% porosity [ 71 , 72 , 73 ]. To the best knowledge of the authors, there is no study which uses the same sensing mechanism to detect the water content in brake fluid.…”
Section: Discussionmentioning
confidence: 99%
“…This study reveals that the sensitivity of aerogel exceeds that of nanofibers. This difference may be attributed to the higher porosity of silica aerogel, which can range from 80% to 99.8% [ 4 , 5 , 6 , 7 , 8 ], compared to that of silica nanofibers, which typically exceed 80% porosity [ 71 , 72 , 73 ]. To the best knowledge of the authors, there is no study which uses the same sensing mechanism to detect the water content in brake fluid.…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at https://www.mdpi.com/article/10.3390/biomimetics8020205/s1: Table S1: A synopsis of each study described within this article, including the authors and publication year, material and tissue type, and testing and mechanical property information, as well as a brief summary, where appropriate, of each research paper reported thus far [29,64,113,[115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148]152,156,157,[159][160][161][162][163][164][165][166]…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The following supporting information can be downloaded at : Table S1: A synopsis of each study described within this article, including the authors and publication year, material and tissue type, and testing and mechanical property information, as well as a brief summary, where appropriate, of each research paper reported thus far [ 29 , 64 , 113 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 152 , 156 , 157 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 170 , 190 ].…”
mentioning
confidence: 99%
“…Previous research suggests alignment of fibers could specifically enhance neuro-regenerative properties. For instance, aligned fibers doped with collagen [ [31] , [32] , [33] ] or growth factors [ 34 , 35 ] have been shown to promote neurite outgrowth. Further, Schwann cells and neurons embedded in hydrogels with aligned fibers exhibited increased neuro-regenerative potential [ 8 , 16 , 36 ].…”
Section: Introductionmentioning
confidence: 99%